CONTEXTUALISATION OF THEOLOGICAL FORMATION - Mattam, Joseph (Asian Horizons, 2018)
This article briefly surveys the a-historical theology of the past and what has led to the inculturation and contextualisation of theology. For centuries theology had become a-historical. In response, South America developed liberation theology; in India besides poverty the presence of many religions forced us to rethink our theology. The recognition of the significance of the context in any learning, and following Vatican II inspiration, the General Congregation of the Jesuits spoke of the need for inculturation, knowledge of the context, and insertion into the culture and life of the people; the South Asian Assistancy of the Jesuits started regional theologates at Ahmedabad, Madras and other places affiliated to either Vidya Jyoti, Delhi or JDV, Pune. They emphasised the context, language of the place, life situation of people, etc. Their basic thrust is to attempt a theology from below, from contact and involvement with the people, especially the poor. A certain degree of involvement in the context has been achieved, experiencing the condition of the life of the people, involvement in their struggles, and the use of the local languages. T.K. John has made significant contribution to theologizing in India.